Effects of Oral ALZ‐801, an Amyloid Oligomer Inhibitor, on Plasma Biomarkers in APOE4 Carriers with Early Alzheimer's Disease: Results of Six‐month Interim Analysis from a Phase 2 Biomarker Study. (20th December 2022) - Abushakra, Susan; Hey, John; Blennow, Kaj; Scheltens, Philip; Reiman, Eric M.; Hort, Jakub; Sheardova, Katerina; Rutgers, Sterre M.; Prins, Niels D.; Dautzenberg, Paul; Pazdera, Ladislav; Power, Aidan; et al.
Abstract: Background: ALZ‐801, an oral, brain‐penetrant small molecule inhibitor of amyloid oligomer formation is being evaluated as a disease‐modifying treatment in APOLLOE4, a Phase 3 trial in APOE4/4 homozygotes with Early Alzheimer's disease (AD). A concurrent Phase 2 study is in progress to study its effects on core AD biomarkers, beta‐amyloid (Aβ) and hyperphosphorylated tau (p‐tau) in APOE4 carriers with Early AD. Method: The Phase 2 study in Czech Republic and Netherlands enrolled APOE4/4 and APOE3/4 subjects with MMSE 22‐30 (CDR‐G 0.5 or 1), who receive ALZ‐801 265 mg tablets BID for 104 weeks. Subjects were amyloid‐PET positive or A+/T+ on CSF assays (ratio of Aβ42/40×10 < 0.61, and p‐tau181 > 61 pg/ml). CSF is evaluated at 52 and 104 weeks, and plasma biomarkers at every visit. Memory tests include the Rey Auditory Verbal Learning Test (RAVLT). Primary outcome is CSF p‐tau181 reduction at 104 weeks; interim analysis on plasma was conducted when all subjects completed 26 weeks. Dr. Blennow's laboratory (Mölndal, Sweden) performed biomarker analyses blinded to clinical data, using Lumipulse (Fujirebio) for CSF and Simoa assays for plasma. Change from baseline in observed biomarker values at each visit were analyzed with paired t‐tests (2‐sided p‐values). Result: Of 84 enrolled subjects (mean 69 years, 51% female, MMSE 25.6), 80 completed 26 weeks. Plasma p‐tau181, the interim primary outcome, showed significant 18% and 29% reductions at 13 and 26 weeks (p = 0.038 and p = 0.028). Reductions of p‐tau181 /Aβ42 were also significant 21% and 30% at 13 and 26 weeks (p = 0.018 and p = 0.022). RAVLT memory scores (immediate + delayed) improved significantly at 26 weeks (p = 0.002). Most common adverse events were mild nausea with no drug‐ related serious events and no ARIA‐E at 52 weeks. Conclusion: Interim Phase 2 plasma biomarker results show significant and robust reductions in plasma p‐tau181 and p‐tau181 /Aβ42 at 26 weeks with memory improvement at 26 weeks. These ALZ‐801 effects on core biomarkers confirm target engagement in AD brain, and support disease modification potential of ALZ‐801. The biomarker effects, oral formulation, and favorable safety without ARIA‐E, make ALZ‐801 an attractive potential treatment for APOE4 carriers with AD.